2004
DOI: 10.1074/jbc.m312475200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Glucokinase Is Required for the Synergistic Action of ChREBP and SREBP-1c on Glycolytic and Lipogenic Gene Expression

Abstract: Hepatic glucokinase (GK) catalyzes the phosphorylation of glucose to glucose 6-phosphate (G6P), a step which is essential for glucose metabolism in liver as well as for the induction of glycolytic and lipogenic genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
348
1
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 400 publications
(380 citation statements)
references
References 61 publications
19
348
1
6
Order By: Relevance
“…It has also been proposed that the mitogen-activated protein (MAP) kinase pathway and the phosphatidylinositol (PI) 3-kinase pathway are involved in the SREBP-1c-mediated FAS gene expression 41,42 and that hepatic glucokinase (glucose-specific hexokinase) is required for the synergistic action of ChREBP and SREBP-1c in lipogenic gene expression. 39 The high hexokinase activity in the transplantation model has already been demonstrated 5 and we have recently also shown, that insulin signalling via the MAP kinase pathway is strongly increased in the FAH. 7 Thus, our in vivo study confirms the observations made in cultured hepatocytes: high levels of insulin and glucose in conjunction with high glucokinase expression, possibly mediated by the MAP kinase pathway, lead to upregulation of the FAS gene.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has also been proposed that the mitogen-activated protein (MAP) kinase pathway and the phosphatidylinositol (PI) 3-kinase pathway are involved in the SREBP-1c-mediated FAS gene expression 41,42 and that hepatic glucokinase (glucose-specific hexokinase) is required for the synergistic action of ChREBP and SREBP-1c in lipogenic gene expression. 39 The high hexokinase activity in the transplantation model has already been demonstrated 5 and we have recently also shown, that insulin signalling via the MAP kinase pathway is strongly increased in the FAH. 7 Thus, our in vivo study confirms the observations made in cultured hepatocytes: high levels of insulin and glucose in conjunction with high glucokinase expression, possibly mediated by the MAP kinase pathway, lead to upregulation of the FAS gene.…”
Section: Discussionmentioning
confidence: 98%
“…FAS gene expression in rat hepatocytes is regulated by both insulin and glucose. It has been suggested that insulin regulation of FAS is at least partly mediated by the basic/helixloop-helix/leucine zipper transcription factor sterol regulatory element-binding protein-1c (SREBP-1c) 38 and that glucose induction of FAS is mediated through a SREBP-1c-distinct transcription factor, designated as either carbohydrate-responsive element-binding protein (ChREBP) 39 or carbohydrateresponsive factor. 40 Interestingly, glucose and insulin stimulate FAS expression synergistically, that is, high glucose levels increase the insulin stimulatory effect, 38 which explains the strong FAS overexpression in our hormonal model.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] In this study, we investigated whether uric acid induced ER stress in liver, and modulation of uric acid-induced ER stress could ameliorate hepatic fat accumulation. We also examined the differential activation of transcription factors responsible for uric acid-induced fat accumulation in hepatocytes with a demonstration of cross-talk between ER stress and oxidative stress.…”
mentioning
confidence: 99%
“…Afin de confirmer le rôle de ChREBP en tant que média-teur majeur de l'action transcriptionnelle du glucose, notre équipe a développé une technique d'ARN interférent (ARNi) permettant d'inhiber sélectivement l'expression de ChREBP. Dans des hépatocytes isolés de souris transfectés avec l'ARNi ChREBP, une forte concentration de glucose (25 mM) n'est plus capable de stimuler l'expression des gènes glycolytiques (L-PK) et lipogéni-ques (ACC, FAS) [16]. De plus, l'accumulation de lipides est fortement diminuée en l'absence de ChREBP dans ces cellules.…”
Section: Identification Du Facteur De Transcription Chrebp Comme Médiunclassified